Historical evolution of cancer genomics research in Latin America: a comprehensive visual and bibliometric analysis until 2023 - Lozada-Martinez, Ivan David; Lozada-Martinez, Luz Miryam; Cabarcas-Martinez, Andrés; Ruiz-Gutierrez, Franklin Kevin; Aristizabal Vanegas, Jose Gabriel; Amorocho Lozada, Katherine Julieth; López-Álvarez, Lina María; Fiorillo Moreno, Ornella; Navarro Quiroz, Elkin (Frontiers in Genetics, 2024)
Background: Cancer genomics, as an interdisciplinary research area within the Global Cancer Research agenda, genomics and precision medicine, its important in research and clinical practice in Latin America. To date, there has been no study investigating evolution of this area in this region. The aim of this study was to evaluate for first time, the historical evolution of cancer genomics research in Latin America.Methods: Bibliometric cross-sectional study of documents on cancer genomics published by Latin American authors until 2023 in Scopus was performed. Statistical and visual analysis was performed with R programming language.Results: A total of 1534 documents were obtained. The first document of cancer genomics research was published in 1997, marking the inception of a 26-year evaluation period that extended until 2023. Among the documents, 74.3% (n=1140) constituted original articles, followed by 22.7% (n=349) classified as reviews. International collaboration was observed in 6.5% (n=100) of the articles. Within the compilation of the ten most prolific authors in this region, 90% of them are from Brazil. This observed pattern extends to affiliations as well, wherein the Universidade de São Paulo emerges as the most active institution (n=255 documents). This arrangement firmly establishes Brazil's prominence as the preeminent country in the region concerning cancer genomics research, showcasing robust collaboration networks both regionally and intercontinentally. An important transition in the studied hot topics over the last 20 years was identified, from the exploration of the human genome and the characterization of genomic and proteomic cancer profiles (1997 -2010) to an indepth investigation of cancer stem cells and personalized medicine (2011 -2023). Among the array of cancer types under study, predominant attention has been directed towards breast, lung, prostate, and leukemia.Conclusions: Over the course of the past 26 years, a favorable and notable evolution has characterized cancer genomics research within Latin America, with Brazil leading the way, which possess a robust network of regional and intercontinental collaboration. Furthermore, the lines of research and hot topics have change in harmony with the region's objectives, strategies, and requisites.